Molybdenum‐Catalyzed Oxidative Cleavage of Raw Poplar Sawdust into Mono‐Aromatics and Organic Acid Esters. Issue 8 (10th July 2019) - Ma, Yangyang; Ma, Jiping; Xia, Fei; Lu, Fang; Du, Zhongtian; Xu, Jie
Abstract: Conversion of non‐edible lignocellulosic biomass into value‐added chemicals is of great significance and also particularly attractive. However, owing to the complexity and inertness, valorization of native lignocellulose remains to be quite challenging. Herein, catalytic oxidative cleavage of raw poplar sawdust was studied, mono‐aromatics and organic acid esters with 34.8 wt% and 27.4 wt% yield respectively were achieved over MoO2 (acac)2 with molecular oxygen, which was suggested to be attributed to a prior cleavage of the carbohydrate fractions. This catalytic oxidation approach demonstrates the feasibility of transformation of raw woody biomass into valuable chemicals. Abstract : It's cool to be a poplar kid : Catalytic aerobic oxidative cleavage of raw poplar sawdust to mono‐aromatics and organic acid esters with the yield of 34.8 wt% and 27.4 wt% was achieved over MoO2 (acac)2 in CH3 OH.